(untitled) (Orfeu, 2023)
Recordings of well-known piano performances have been analysed through technology-generated MIDI data — offering insights into certain features of performance, such as timing, dynamics, articulation, and pedalling — nevertheless, the application of digital technologies to the actual process of studio-based piano learning and teaching remains under-researched. A research study conducted in Brazil explored the use of visual feedback alongside three teacher-student pairs in the higher education context. The technology feedback system involved a digital piano connected to a laptop computer running Digital Audio Workstation (DAW) software via a Musical Instrument Digital Interface (MIDI) interface and an additional computer screen. Three related datasets were collected: (i) digital video recordings of the piano lessons (n = 6), (ii) audio recordings of semi-structured interviews with participants (n = 12) and (iii) MIDI data saved in the DAW software . Qualitative data analyses (QDA) encompassed using a multi-methods approach. This paper presents the results of the analysis of observational data and MIDI data where the piano lesson focus was to work on piano articulation. Findings suggest that when subtle aspects of articulation are made visible to both teacher and student using this technology system, both become more aware of these issues. In addition, when visual feedback is used, the lesson focus can be clearer, and discussions between teacher and student become more effective.